Upper Class Elementary School Student Engagement in Math Subject Merdeka Curricula: Post Covid Study Case in Jakarta Province Indonesia - Riana Bagaskorowati; Tresnani; Widiya Alita; Novi Nur Samiadi; Novriko Burhan (Universitas Pendidikan Ganesha, 2023)
The Merdeka Curriculum is a new paradigm curriculum launched in 2020 by the Minister of Education of the Republic of Indonesia. The study aimed to measure post-covid 19 high school students in mathematics in Jakarta Province, Indonesia. This study examined the four dimensions of the student engagement instrument (SEI) and was validated using confirmatory factor analysis/CFA through a structural equation model (SEM). This type of research is quantitative. The quantitative method used is proportional sampling, with 503 samples spread over 5 (five) regions. The data collection method uses a survey. The instrument used in collecting data is a questionnaire. Data analysis techniques using qualitative and quantitative descriptive analysis. The study's results, namely the predictive validity of the results on the four dimensions of student engagement, were assigned a score of 0.709 for CE (cognitive engagement). 0.837 for BE (behavioral engagement). 640 for EE (emotional involvement). 0.412 for SE (social engagement). We estimated Cronbach's alpha as the overall reliability of student engagement (SEI) on the four SE dimensions with moderate height at 0.74 for CE (cognitive engagement). 0.82 for BE (behavioral engagement). .89 for EE (emotional involvement). 0.73 for SE (social engagement). The benefits of student engagement are helpful for school teachers to measure the effectiveness of student learning activities, and the teacher-student relationship will be warmer and more profound.